183 Novel OPG Protein Interactions Regulate Survival, Proliferation And Pah-associated Gene Expression in Pulmonary Arterial Smooth Muscle Cells. (31st May 2014) - Dawson, Sarah; Pickworth, Josephine; Rothman, Alex; Iremonger, James; Arnold, Nadine; Lawrie, Allan
Abstract : Introduction: Pulmonary arterial hypertension (PAH) is a devastating disease with a high mortality and prognosis worse than many cancers. Pathologically, PAH is characterised by progressive arteriole remodelling driven by pulmonary artery smooth muscle cell (PASMC) proliferation and migration. Although current treatments alleviate symptoms, they do not reverse the underlying progressive pulmonary vascular proliferation. We have previously shown that the secreted glycoprotein osteoprotegerin (OPG, TNFRSF11B) is increased within pulmonary vascular lesions and serum from patients with idiopathic PAH, and promotes the proliferation and migration of PASMCs in vitro . Recent experiments have shown that administration of an anti-OPG antibody can prevent and reverse PAH in rodent models of disease. However, how OPG signals to mediate PASMC phenotype remains unknown. We hypothesise that OPG mediates these effects through a previously undescribed cell surface receptor. We aim to identify this receptor on PASMC and characterise the OPG signalling cascade leading to the proliferative phenotype. Methods: Quiesced PASMCs (Lonza, Basel, Switzerland) were stimulated with 0.2% FCS (negative), and OPG (50 ng/ml) for 10 and 60 min. Phosphorylation targets were identified from protein lysates by Kinex antibody microarray (Kinexus, Canada). Selected targets were verified by western blotting. Transcriptomic analysis of PASMCs stimulated with OPG for 6 h was performed using an RNA expression microarray (Agilent) and confirmed by TaqMan RT-PCR. Novel OPG binding proteins were identified following reverse transfection of HEK293 cells with 2054 human membrane proteins (Retrogenix, Sheffield, UK) and confirmed in PASMC by co-immunoprecipitation. To assess the effect of Fas blockade, proliferation was assessed in PASMCs pre-incubated with Fas neutralising antibody (500 ng/ml) 30 min before 72h stimulation with OPG. Results: OPG stimulation of PASMC resulted in significant activation of CDK4 and 5, HSP27 and ERK1/2, and significant decrease in phospho-mTOR. OPG increased TRAIL, PDGFRA, TNC, Cav-1 and reduced VIP receptor gene expression. Four novel OPG interactions with IL1RAP, Fas, TMPRSS11D and GAP43 were identified by the Retrogenix cell microarray. We have confirmed OPG interaction with IL1RAP and Fas in PASMC by co-immunoprecipitation. Fas protein expression is elevated in the pulmonary artery and right ventricle of IPAH patients. Fas RNA expression is increased in PASMCs from IPAH patient lungs. Furthermore, blocking Fas with a neutralising antibody reduces OPG-induced proliferation, PDGFRA and TNC RNA expression. Conclusions: These data highlight novel binding partners for OPG. In particular the OPG-FAS interaction regulates a diverse and important intracellular signalling cascade by which OPG regulates proliferation, apoptosis and autophagy proteins, and PAH associated genes in PASMC. These data further highlight therapeutic potential of targeting OPG in PAH.